Bytelearn - cat image with glassesAI tutor

Welcome to Bytelearn!

Let’s check out your problem:

Rewrite the function by completing the square.

{:[f(x)=x^(2)+2x+26],[f(x)=(x+◻)^(2)+◻]:}

Rewrite the function by completing the square.\newlinef(x)=x2+2x+26 f(x) = x^2 + 2x + 26 \newlinef(x)=(x+)2+ f(x) = (x + \square)^2 + \square

Full solution

Q. Rewrite the function by completing the square.\newlinef(x)=x2+2x+26 f(x) = x^2 + 2x + 26 \newlinef(x)=(x+)2+ f(x) = (x + \square)^2 + \square
  1. Identify coefficient of x: Identify the coefficient of x to complete the square.\newlineThe coefficient of x is 22. To complete the square, we need to find the value that makes x2+2xx^2 + 2x a perfect square trinomial.
  2. Calculate value to complete the square: Calculate the value needed to complete the square.\newlineWe take half of the coefficient of xx, which is 22=1\frac{2}{2} = 1, and then square it to get 12=11^2 = 1. This is the value we will add and subtract inside the parentheses to complete the square.
  3. Rewrite the function: Rewrite the function by adding and subtracting the calculated value inside the parentheses.\newlinef(x)=x2+2x+11+26f(x) = x^2 + 2x + 1 - 1 + 26\newlineNow we have added and subtracted 11, which does not change the value of the function, but allows us to complete the square.
  4. Factor and simplify: Factor the perfect square trinomial and simplify the constant terms.\newlinef(x)=(x+1)21+26f(x) = (x + 1)^2 - 1 + 26\newlinef(x)=(x+1)2+25f(x) = (x + 1)^2 + 25\newlineWe have factored the trinomial x2+2x+1x^2 + 2x + 1 into (x+1)2(x + 1)^2 and combined the constants 1-1 and 2626 to get +25+25.

More problems from Solve a quadratic equation by completing the square